Analysis of Inhibiting Factors in the Development of the Bukik Panjang Patah Sambilan Agro Tourism Area, Padang Alai Bodi Village, East Payakumbuh District - Suwandi, Irwan; Putera, Roni Ekha (IJBLE Scientific Publications Community Inc., 2024)
The increase in community welfare is expected to be directly proportional to the economic growth experienced by the area. One thing that is hoped for is the development of tourism areas. The aim of this research is to analyze the factors inhibiting the development of the Bukik Panjang Patah Sambilan agrotourism area,Padang Alai Bodi Village, East Payakumbuh. Phenomoneological qualitative research design. Research data was obtained through observation, interviews (In-depth interviews),documentation. The research results showed that there were 5 inhibiting factors in developing agrotourism areas, namely lack of facilities and infrastructure to support the development of agrotourism areas, lack of budget, insufficient number and competency of human resources, dependence on government, access to locations of agrotourism areas. Based on the results of this research, cooperation between the community and the government is needed to recognize the existing problems, then socialization can be carried out regarding the use of agro-tourism areas which can later grow the community's economy.